Lamp spectrum and spatial brightness at photopic levels: Investigating prediction using S/P ratio and gamut area. (August 2015) - Fotios, S; Atli, D; Cheal, C; Hara, N
An experiment was carried out to investigate spatial brightness at photopic levels under lighting of different spectral power distributions. One aim was to replicate the experiment reported in 1990 by Berman et al. demonstrating that light with a higher scotopic / photopic (S/P) ratio would be perceived as brighter. In addition, a third SPD was included to investigate gamut area and two additional procedures were employed to provide concurrent validity of the findings. It was concluded that while lighting of higher S/P ratio was brighter, the S/P ratio alone was insufficient to predict spatial brightness. A metric for the chromatic contribution is also needed, this being provided by gamut area in the current work.